Upaya Meningkatkan Efektivitas Perlindungan Hukum Anak Korban Bullying di Lingkungan Sekolah - Husnul Hamdi Yonas Yonas; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Bullying in schools poses a serious threat to child development and demands effective protection. In Indonesia, despite the existence of a comprehensive legal framework and child protection regulations, implementation in the field remains suboptimal. This study aims to explore the alignment between the legal framework and child protection regulations concerning bullying and to identify inhibiting factors and formulate efforts to enhance the effectiveness of protection for child victims in school environments. Utilizing a qualitative approach with an analysis of legal documents, including legislation, prior research, and case reports, as well as an analysis of bullying cases in Indonesia, this study reveals discrepancies between policies implemented in the field and existing regulations. Factors such as low public awareness, complex legal processes, a culture of silence, and lack of support for victims constitute major obstacles to providing maximum protection. Recommendations for improving the effectiveness of protection include strengthening the role of schools, raising public awareness, and simplifying reporting procedures. This study is expected to provide guidance for policymakers in their efforts to enhance the protection of children who are victims of bullying in Indonesia.